Indications for use of thoracic, abdominal, pelvic, and vascular damage control interventions in trauma patients: A content analysis and expert appropriateness rating study. Issue 4 (October 2015) - Roberts, Derek J.; Bobrovitz, Niklas; Zygun, David A.; Ball, Chad G.; Kirkpatrick, Andrew W.; Faris, Peter D.; Parry, Neil; Nicol, Andrew J.; Navsaria, Pradeep H.; Moore, Ernest E.; Leppäniemi, Ari K.; Inaba, Kenji; et al.
Abstract : BACKGROUND: The use of abbreviated or damage control (DC) interventions may improve outcomes in severely injured patients when appropriately indicated. We sought to determine which indications for DC interventions have been most commonly reported in the peer-reviewed literature to date and evaluate the opinions of experts regarding the appropriateness (expected benefit-to-harm ratio) of the reported indications for use in practice. METHODS: Two investigators used an abbreviated grounded theory method to synthesize indications for 16 different DC interventions reported in peer-reviewed articles between 1983 and 2014 into a reduced number of named, content-characteristic codes representing unique indications. For each indication code, an international panel of trauma surgery experts (n = 9) then rated the appropriateness of conducting the DC intervention of interest in an adult civilian trauma patient. RESULTS: The 424 indications identified in the literature were synthesized into 101 unique indications. The panel assessed 12 (70.6%) of the coded indications for the 7 different thoracic, 47 (78.3%) for the 7 different abdominal/pelvic, and 18 (75.0%) for the 2 different vascular interventions to be appropriate for use in practice. These included indications for rapid lung-sparing surgery (pneumonorrhaphy, pulmonary tractotomy, and pulmonary wedge resection) (n = 1); pulmonary tractotomy (n = 3); rapid, simultaneously stapled pneumonectomy (n = 1); therapeutic mediastinal and/or pleural space packing (n = 4); temporary thoracic closure (n = 3); therapeutic perihepatic packing (n = 28); staged pancreaticoduodenectomy (n = 2); temporary abdominal closure (n = 12); extraperitoneal pelvic packing (n = 5); balloon catheter tamponade (n = 6); and temporary intravascular shunting (n = 11). CONCLUSION: This study identified a list of candidate appropriate indications for use of 12 different DC interventions that were suggested by authors of peer-reviewed articles and assessed by a panel of independent experts to be appropriate. These indications may be used to focus future research and (in the interim) guide surgical practice while studies are conducted to evaluate their impact on patient outcomes. Abstract : Supplemental digital content is available in the text.